The Role of Interactive Digital Media in Enhancing Conceptual Understanding of History in Secondary Schools - Setiawan, Johan (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
History learning in secondary schools often faces challenges, such as low student interest and limited understanding of abstract and chronological concepts. This study aims to examine the role of interactive digital media in improving students' conceptual understanding of history based on findings from previous studies. The research employed a literature review approach, gathering relevant scholarly articles, journals, and research reports related to history education and the use of digital media. The findings indicate that interactive digital media, including historical simulations, interactive quizzes, and visual animations, can enhance students’ conceptual understanding, learning motivation, and engagement in the learning process. These results underscore the importance of integrating digital media as an innovative instructional strategy that supports the development of students’ critical thinking and analytical skills. This study recommends the systematic implementation of interactive digital media within the history curriculum to foster more engaging and effective learning experiences.